(untitled) (Nordic Journal of African Studies, 2010)
In a complex postcolonial multilingual context, such as Cameroon, many languages are available to the speakers and even compete to be used. This study investigates linguistic choices made by Cameroonians selected according to some sociolinguistic factors, their reasons for choosing or rejecting the languages used in Cameroon and the political, sociocultural and sociolinguistic ideologies such choices are likely to convey.